Diversely Substituted Indoloazepinones and Indoloazocinones: A Post-Ugi Gold-Catalyzed Regioselective Carbocyclization Approach - Vachhani, Dipak D.; Kumar, Amit; Modha, Sachin G.; Sharma, Sunil K.; Parmar, Virinder S.; Van der Eycken, Erik V. (Synthesis, 2015)
A post-Ugi gold-catalyzed regioselective intramolecular carbocyclization strategy is reported. A better cationic gold system, compared to our previous report, has been optimized and utilized. The method presented exhibits excellent functional group compatibility including bulky substitutions on alkynes and allows the direct access to indoloazepinones and indoloazocinones in good to excellent yields.
Keywords: post-Ugi; gold; indoloazepinone; indoloazocinone; carbocyclization